KANDUNGAN GIZI MAKANAN SAPIHAN BAYI DARI UBI JALAR DENGAN KOMBINASI KACANG HIJAU DAN PISANG AMBON - Eny Idayati (Politeknik Pertanian Negeri Kupang, 2009)
Nutrient Contents in Sapihan Baby Food From Jalar Sweet Potato With Green Peanut Combination and Ambon Banana. This research aims to detect nutrient composition of sapihan food shaped jalar sweet potato cracker with green peanut treatment and Ambon Bananathat allocated for children under five with make use food source exist in Nusa Tenggara Timur. This research is supposed can increase product added value, power saves, and nutrient value in order to increase family nutrient fulfillment especially in children under five, increase economy welfare and family social and society.Research method that used complete random plan (RAL) factorial pattern with 2 factors. First factor that is green peanut that consist of 3 level that is: 25%,50%, and 75%. second factor Ambon banana consists of 3 level that is: 12,5%, 25% and 37,5%. Effort is repeated as much as 3 times. Research result data is cultivated, then analyzed to use unity test (anova). Furthermore treatment difference at test with difference smallest real (BNT) in standard 0,05.To detect influence from each treatment, so observation towards cracker characteristics is done to pass objective test that is calorie, protein, vitamin A and vitamin C with water contents.Green peanut treatment and Ambon banana towards baby cracker from jalar sweet potato flour in best objective analysis that is: 1)Sum of calorie in green peanut treatment 25% and Ambon banana 12,5% (K1P1) is 531,862 cal/100 gr, 2)Protein contents in treatment green peanut 75% and Ambon banana 37,5% (K3P1) is 11,627%, 3)Vitamin A contents in green peanut treatment 25% and Ambon banana 12,5% (K1P3) is 2505,99 micro gr/100 gr, 4)Vitamin C contents in green peanut treatment 25% and Ambon banana 12,5% (K3P1) is 126,258 micro gr/100 gr and 5)Water contents in green peanut treatment 25% and Ambon banana 12,5% (K1P1) is 5,81087%.Keywords: nutrient, sapihan food, jalar sweet potato